THE EFFECT OF CONTACT TIME AND OZON DOSE TO POLUTANTS REDUCTION IN HOSPITAL WASTEWATER (Universitas Negeri Semarang, 2018)
In Indonesia, Hospital wastewater treatment generally use biological process followed by chlorination process. Chlorination process has a negative impact on the aquatic environment that is cause death of other microorganisms by the residual chlorine. On the other hand, ozone is more effective than chlorine in killing microorganisms and other pollutants in hospital wastewater. The objective of research is to determine the effect of contact time and dose of ozone to reduction of pollutants (BOD, COD, free Ammonia and Phenol) in hospital wastewater. The experiment was carried out using an ozone reactor containing 'packing', an ozone generator as an ozone gas supplier. The experimental material is a hospital wastewater containing BOD, COD, Phenol and Ammonia free. The experimental variables used were: Contact time (1, 2, and 3 min), Dose of ozone (10, 15, and 20 mg/ L). Experiments were done by flowing hospital waste water at the top of the reactor ozone at certain rate and simultaneously flowed ozone gas from an ozone generator in the bottom of the ozone reactor so that it contacts the fluid in counter-current to the surface of the packing material (packing) in an ozone reactor. By adjusting the flowrate of the wastewater and the height of the packing, it can be determined the amount of contact time and ozone dose. Furthermore, by measuring the amount of pollutant concentration on the influent and effluent of the ozone reactor, it can be obtained the amount of removal in the pollutant concentration of the hospital wastewater.The results showed that contact time and ozone dose influence the decrease of pollutant concentration in hospital wastewater where contact time at 3 minutes and ozone dose 20 mg/L and ozonation time 15 minutes can reduce of pollutants concentration as BOD (97%), COD (98%), Ammonia free (97%), and Phenol (96%).